SARS-CoV-2-induced myocarditis in pediatric patients: A 10-case series from Sanandaj, Iran: Pediatric myocarditis - Rahimi-Darehbagh, Ramyar; Karimi, Avat; Behzadi, Shirin; Mohammadi, Shilan; Khalafi, Behzad; Babahajiani, Media; Moradveisi, Borhan (Chronic Diseases Journal, 2024)
BACKGROUND: Fever, cough, and acute lung involvement are severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) symptoms. Children can be asymptomatic virus carriers and may contribute to the prevalence of coronavirus disease 2019 (COVID-19). Like other viral diseases, the involvement of different heart parts is also seen in this disease. Myocarditis is an inflammation of the myocardium, usually caused by a virus. The primary aim of this study is to investigate the occurrence and clinical manifestations of myocarditis among pediatric patients infected with SARS-CoV-2 in Sanandaj, Iran. CASE REPORT: In this study, COVID-19 myocarditis cases in Be’sat Hospital, Sanandaj, were documented. Ten pediatric patients with a definitive diagnosis of COVID-19 who were admitted to Be’sat Hospital in Sanandaj in 2020 were included in this study based on clinical trials after seeking echocardiography and confirming myocarditis. The mean age of these 10 study cases was 7.1 years (2 to 13 years). The most common symptoms were fever, respiratory distress, cough, and vomiting. Ceftriaxone, intravenous immunoglobulin (IVIG), and dopamine were the main interventions in these cases. After these cases, all general practitioners and pediatricians in the province and the country were given the necessary warnings. Based on the results, COVID-19 infections, like viral infections, such as enterovirus and adenovirus, are known as the main causes of myocarditis, which appear as local or general myocardial inflammation, tissue necrosis, and ventricular dysfunction. CONCLUSION: A direct viral attack and overactive immune responses in viral myocarditis can harm heart tissue. Therefore, in COVID-19-infected individuals, serial symptom evaluation and monitoring are necessary.